2020
DOI: 10.1098/rspb.2020.1377
|View full text |Cite|
|
Sign up to set email alerts
|

The efficacy of natural selection in producing optimal sex ratio adjustments in a fig wasp species

Abstract: Ever since Darwin's discovery of natural selection, we expect traits to evolve to increase organisms' fitness. As a result, we can use optimization models to make a priori predictions of phenotypic variation, even when selection is frequency-dependent. A notable example is the prediction of female-biased sex ratios resulting from local mate competition (LMC) and inbreeding. LMC models incorporate the effects of LMC and inbreeding. Fig wasp sex ratio adjustments fit LMC predictions well.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 49 publications
0
24
2
Order By: Relevance
“…Possible factors may include the stronger effects of LRE on even more female‐biased sex ratios as shown in the multiplicative functional forms, or it may even be suggested that some constraints limit the facultative sex ratios in M. australica (Shuker and West 2004; Greeff et al. 2020). Nonetheless, these sex ratios are still more female biased than predicted by our models.…”
Section: Discussionmentioning
confidence: 99%
“…Possible factors may include the stronger effects of LRE on even more female‐biased sex ratios as shown in the multiplicative functional forms, or it may even be suggested that some constraints limit the facultative sex ratios in M. australica (Shuker and West 2004; Greeff et al. 2020). Nonetheless, these sex ratios are still more female biased than predicted by our models.…”
Section: Discussionmentioning
confidence: 99%
“…1), but more female-biased than the prediction by a model incorporating dispersal status (Abe et al in preparation). It may even be the case that Melittobia australica are unable to facultatively adjust sex allocation in response to local patch size due to some constraints (Shuker & West 2004; Greeff et al 2020). Despite this, our models offer a useful framework to study the evolution of sex ratios under LRE and allow further development of theoretical work.…”
Section: Discussionmentioning
confidence: 99%
“…Females are proovogenic meaning all their eggs are mature as soon as they leave their natal fig [52]. Females readily enter the fig and oviposit if they are placed on a receptive fig allowing experimental manipulation of foundress numbers [18,19,26,41,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. Females do not invest in offspring rearing and no egg dimorphism is known [52], meaning the investment in the two sexes can be equated with the number of eggs of each sex that were laid.…”
Section: The Fig Wasp Model Systemmentioning
confidence: 99%
“…For pollinating fig wasps, a single foundress should lay enough sons to ensure all her daughters will be mated, but in addition, there must also be enough males to chew an exit hole through the fig wall [16]. Several studies have found that all females are not always mated [49,50,68,70,[72][73][74][75] and sometimes too few males are laid to Within each graph, each shape refers to a different species. We obtained 95% CIs in five ways indicated by the colours of the vertical lines and in order of preference as data allowed: (1) In black, e a /(e a + 1) where a is given by the generalized linear model coefficient ± 1.96x(se of the coefficient).…”
Section: The Fig Wasp Model Systemmentioning
confidence: 99%